Identification of CKS1B as a prognostic indicator and a predictive marker for immunotherapy in pancreatic cancer - Li, Lincheng; Wang, Jing; Zhang, Zhuochao; Yang, Qiyue; Deng, Zhaoda; Zou, Wenbo; Ge, Xinlan; Pan, Ke; Li, Chonghui; Liu, Rong (Frontiers in Immunology, 2022)
As a regulatory subunit of cyclin kinase, CKS1B promotes cancer development and is associated with poor prognosis in multiple cancer patients. However, the intrinsic role of CKS1B in pancreatic cancer remains elusive. In our research, CKS1B expression in pancreatic tumor tissue was higher than that in normal tissue by TCGA, Oncomine and CPTAC databases analysis. Similar result was verified in our center tissues by qRT-PCR. CKS1B expression was closely relevant to histologic grading, prognosis, and TMB. GSEA showed that CKS1B mainly participated in the regulation of autophagy and T cell receptor signaling pathway. Furthermore, CIBERSORT analysis showed that there was a strong correlation between CKS1B expression and tumor immune cells infiltration. Drug sensitivity analysis showed that patients with high CKS1B expression appeared to be more sensitive to gemcitabine, 5-fluorouracil, and paclitaxel. We then investigated cell viability and migratory ability by CCK8 and transwell assay, respectively. Results indicated that CKS1B knockdown by short hairpin RNA significantly reduced pancreatic cancer cell viability and invasion via regulating PD-L1 expression. In conclusion, our research further demonstrates the role of CKS1B in pancreatic cancer and the signaling pathways involved. The association of CKS1B with immune infiltration and immune checkpoint may provide a new direction for immunotherapy of pancreatic cancer.